Tropical almond antioxidant gels mitigate the adverse effects of strong whitening agents on immediate bonding - Verónica Cecilia MEJÍA; Vitória Moraes MARQUES; Tamara Gonçalves de ARAÚJO; Lara Cecília de MOURA; Ana Cristina de Mello FIALLOS; Mary Anne Sampaio de MELO; Sérgio Lima SANTIAGO; Vanara Florêncio PASSOS (Brazilian Oral Research)
Abstract Radicals from tooth whitening products can reduce bond strength, posing challenges for dentists when a bonding procedure must be performed in teeth immediately after whitening. This study aimed to evaluate the antioxidant activity (AA) of Terminalia catappa Linn (TCL) leaf extract as a potential agent to mitigate the negative impact of high-concentration whitening agents on immediate bonding performance. The AA of green and ripe leaf extracts was measured using the 2,2-di-phenyl-1-picrylhydrazyl radical scavenging capacity assay (DPPH). To determine the TCL influence on bond strength, six groups of bovine enamel blocks (n=10) were created. Group 1 was the positive control (unbleached enamel), while Group 2 was the negative control (no antioxidant treatment). Groups 3 to 6 were bleached and treated with 10% sodium ascorbate (SA) or 0.1%, 0.2%, and 0.3% TCL gels. Adhesion was conducted using a two-step conventional system and dental composite resin. Microtensile testing was performed after 24 hours, and data were analyzed by one-way ANOVA with Tukey’s post hoc test (p > 0.05). From the DPPH assay, results with IC50 < 50 µg/mL indicate high AA for all tested extracts. This method established a difference of around 12 times more AA for the TCL-hydroalcoholic extract of green leaf to the aqueous extract of ripe leaves. There were no significant differences in bond strength among groups treated with TCL-hydroalcoholic extract of green leaf gels (p > 0.05) and unbleached enamel. Tropical almond-derived antioxidant gels emerge as a promising strategy to enhance immediate bond strength on enamel after high-concentration in-office whitening treatments.